Training and supervision in sport and exercise psychology - McCarthy, Paul 1977-; Gupta, Sahen; Burns, Lindsey; McCann, Bryan (Routledge, 2024)
This book presents choices and challenges for trainees and supervisors, such as training and supervision mixing the science of doing sport and psychology with the art of decision-making to deliver services to athletes.